Use of gonadotropins in ovarian stimulation in Spain: Delphi consensus - Gorka Barrenetxea; Cora Hernández; Julio Herrero; Luis Martínez Navarro; Manuel Muñoz; José María Rubio; Fernando Sánchez; Jesús Zabaleta (Taylor & Francis Group, 2023)
Two-round Delphi study carried out in Spain. Three theme-based blocks were set out: 1) Patient profiles: therapeutic goal and parameters to be analysed according to POSEIDON patient profiles; 2) Ovarian stimulation protocols with antagonists: monotherapy (FSH) vs combined therapy (FSH + LH/HMG); 3) Safety and effectiveness of the devices. The antral follicle count and the anti-Müllerian hormone level were considered indicators that can be used to predict ovarian response. More than 80% of the participants agreed that FSH monotherapy is the recommended regimen in normal/hyper-responsive patients of < 35 years of age; that 150-300 IU is the dose to be used in ovarian stimulation in monotherapy depending on clinical parameters; and that FSH monotherapy improves patients' comfort compared to two combined drugs. It was unanimously considered that the type of device used by the patient influences the comfort of the treatment.IMPACT STATEMENT What is already known on this subject? There is currently no consensus on the optimal treatment for controlled ovarian stimulation for patients undergoing IVF which leads to highly variable clinical practices. What the results of this study add? This study's strong point is that, since it is a consensus, it has been possible to include more topics than would normally be dealt with in a systematic review or guidelines, which are generally based on a strict method that restricts the scope of the research. Experts have reached a consensus on most of the statements and based on these they have issued consensus statements that will enable the optimal use of gonadotropins in IVF. What the implications are of these findings for clinical practice and/or further research? This Delphi consensus provides a real-life clinical perspective on gonadotropin usage in IVF.